WeCare : the district nurse and self-organising home care teams - when efficiency meets professional discretion - Comiteau, Lauren, (SAGE Business Cases., 2018)
In late 2016, Bas Smit, CEO of WeCare, a large Dutch regional care organisation providing home care, intramural nursing home care and extramural social care, had just returned from a high-level funding session organised by the Dutch Healthcare Authority. In addition to people from the care sector, the meeting included representatives from insurance companies, government agencies and healthcare providers-all there on a rainy afternoon to assess recent attempts by care providers to improve the quality and personalization of home care while cutting costs.This case explores WeCare's model of self-organisation and addresses key challenges in dealing with issues of innovation, costs and efficiency, quality of care and the job quality of care workers. This case shows the complex regulatory and financial environment in which an existing home care organisation aims to develop and adapt by introducing self-organising teams.